Analisis Pengendalian Kualitas Mutu Produk Sebelum Eksport Dengan Mengunakan Metode Six Sigma Pada PT. Nichindo Manado Suisan - Baguna Tenny; Lucky F. Tamengkel; Danny D. S. Mukuan (Universitas Sam Ratulangi, 2018)
PT. Nichindo Manado Suisan is a foreign private export company engaged in food products. PT produces various products that are produced are katsuobuhi products, and hanakatsuo derivatives, itokezuri made from skipjack fish, this research aims to find out how to control and what factors cause defective products. According to Gaspersz (2005: 310) six sigma is a vision of improvingquality towards a target of 3.4 failures per million opportunities for every transaction of goods and product services, in the research in January and April 2018 found 10234 kg defective products from 80797 kg production. there is a further research conducted using the Six Sigma method which is a structured methodology to reduce process variation while reducing product defects sothat improvements are expected in the products produced with the aim of Analyzing quality control before export by PT. nichindo manado suisan and Knowing what factors cause quality to be less good by using rare DMAIC Six Sigma is Define, Measure, Analyze, Improve, Control. In the define phase, you know what kind of defects in production are packaging. Then in the measure phasethrough the Pareto diagram it can be the most dominant damage. Then in the analyze stage there are some root causes of the problem, among others are the lack of supervision from the company, and the lack of employee skills, so that in the improve phase there will be some quality improvement proposals, and stage of control The company must continue to make recommendations for continuous improvement of controls so that the number of defects can continue to decrease, based on the results of data collection, analysis and discussion caused by a less skilled workforce, therefore the company must carry out strict supervision.Keywords: Quality control before export, employee skills